Single nucleotide polymorphisms of follicle-stimulating hormone receptor promoter and their impacts to the promoter activities (Medical Journal of Indonesia, 2004)
Women of reproductive ages are varies in their responses to exogenous FSH stimulations. The difference of FSHR genotype due to the polymorphisms in exon 10 is one of its significant factors. To know further whether the core promoter of FSHR is also polymorphic and to know whether those polymorphisms influence the promoter activity, we did polymorphism screening of FSHR promoter to 262 women undergoing IVF/ICSI, followed by functional study to know the impact of polymorphisms to the promoter activity. This study indicated that the core promoter of human FSHR is polymorphic. We found five SNPs at positions –29, –37, –114, –123 and –138 in addition to the variety number of adenines. Polymorphism at position –123 significantly decreased the promoter activity, in contrast, polymorphism at position –37 and –138 significantly increased the promoter activity, whereas polymorphism at position –29, –114 and short adenines stretch did not significantly influence the promoter activity. The differences of the promoter activities due to polymorphisms might change the ovarian sensitivity to FSH. (Med J Indones 2004; 13: 205-14)